Fungal–plant interaction: a pathogenic relationship between Ganoderma segmentatum sp. nov. and Vachellia nilotica - Umar, Aisha; Yuan, Wanlan; Lu, Junxing; Ameen, Fuad (Frontiers in Microbiology, 2024)
The diversity of Ganoderma is still in the dark, and a little information regarding this genus is available due to fungiphobia and morphological plasticity. To fill this gap, an ongoing study aims to gather the collections and identification of this genus by means of nuclear ribosomal DNA regions called "Internal Transcribed Spacer" (ITS1-5.8S-ITS2 = ITS). In this work, a new species, G. segmentatum sp. nov. was found on the dead tree trunk of the medicinal plant, Vachellia nilotica. The combination of morpho-anatomical characteristics and phylogenetic analyses described this species. This new species was closely matrixed to G. multipileum, G. mizoramense, and G. steyaertanum with a 99% bootstrap value and a separate branch in the phylogenetic tree of this study. Morphologically, G. segmentatum can be distinguished by its frill-like appearance towards the margin of basidiome. Wilt or basal stem rot, a serious disease of trees caused by Ganoderma species and V. nilotica, is brutally affected by this disease, resulting in a substantial loss in health care. This Ganoderma species severely damaged V. nilotica via deep penetration of mycelium in the upper and basal stems of the host species. The pathogenic observational descriptions of G. segmentatum on dead tree trunks indicated the exudation of viscous reddish-brown fluid from the basal stem portion, which gradually extended upward. Decay, stem discoloration, drooping of the leaves, and death are the characteristic symptoms of this disease, which severely damaged the medicinal tree of V. nilotica.